Person-centered evaluation of positive body image among Chinese nursing students: Associations with body appreciation, self-concept clarity, and negative affect - Zhang, Ting; Su, Dan; Li, Shuwen; Yang, Yajuan; Li, Huiping (Frontiers in Psychology, 2023)
Background: Nowadays, the effect of body image (BI) on negative affect among nursing college students has been ignored. This study used person‐centered methods to evaluate the profiles of body appreciation (BA) among Chinese nursing students. We explored the predictive factors of these profiles and examined the difference in negative affect among the profiles. Methods: A cross-sectional survey study was conducted in a university in Anhui province, China. Five hundred and forty-one Chinese nursing students from a nursing college of a larger university completed this survey. Participants completed the Sociodemographic Characteristics Questionnaire, the Self-concept Clarity Scale, the Body Appreciation Scale-2, and the Depression Anxiety Stress Scale. Latent profile analysis was employed to classify the BA profiles, and multinomial logistic regression analyses were conducted using the three-step regression and Bolck- Croon- Hagenaars method to test the relationship between the latent profiles of BA, several covariates (including gender, age, year of schooling, residence, academic achievement level, interpersonal relationship status, whether the student is an only child, duration of use of social media platforms, body mass index (BMI), and self-concept clarity (SCC)), and negative affect. Results: Analysis resulted in a four-profile model that included a “low BA” group (14.42%), an “upper medium BA” group (36.41%), a “lower medium BA” group (36.97%), and a “high BA” group (12.20%). SCC, years of schooling, interpersonal relationship status, and BMI were found to be the predictive factors of BA profiles. The four profiles differed in levels of stress, depression, and anxiety. Conclusions: Our study showed that more than half of nursing students were dissatisfied with their BI and the predictive factors evaluated and negative affect were associated with the profiles of BA. Nursing faculties should take measures to help students develop a more appropriate awareness of nursing aesthetics, a healthier lifestyle, a better interpersonal relationship with family members and peers, and a clearer self-concept to promote body appreciation and reduce negative affect related to BI.